Two new species of Tomocerus ocreatus complex (Collembola, Tomoceridae) from Nanjing, China - Yu, Daoyuan; Yao, Jin; Hu, Feng (Zootaxa, 2016)
Two new species of Tomocerus Nicolet, 1842 are described from Nanjing, China. Tomocerus qinae sp. nov. is similar to the Vietnamese species Tomocerus ocreatus, but is different from the latter mainly in the colour pattern, the length of antennae, and the pattern of ungual teeth. Tomocerus qixiaensis sp. nov. is similar to Tomocerus ocreatus and Tomocerus qinae sp. nov., but can be distinguished from them by the short antennae and the blunt prominent macrochaetae on manubrium and dens. DNA barcode sequences of the new species are provided.